Surat al-Ikhlāṣ dalam Kitab Khazīnat al-Asrār - Rahmatullah Rahmatullah (JOURNAL OF QUR'AN AND HADITH STUDIES, 2018)
This paper discusses the magic aspects of surah al-Ikhlas in the book Khazīnat al-Asrār. This qualitative research answers what aspects of surah al-Ikhlas contained in this book. Through the analysis of Surah Al-Ikhlāṣ in the book, there are at least a few important points. First, the book affirms that the practice of magic in Islam is not a tradition that comes from outside, but it comes from the internal traditions of Muslims in which they are the arguments of authentic hadiths. Secondly, the Quran is believed to be the word of God provides magic values for its readers. It encourages reading certain letters, use as away to resould problems. encountered can be resolved. Thus, the mechanism of action is the same as magic, only it is packaged using Quranic verses.